Role of Immunohistochemistry in the Subtyping of Periampullary Adenocarcinoma. (September 2019) - Bakshi, Neha; Dhawan, Shashi; Nundy, Samiran; Rao, Seema; Chopra, Prem; Bhalla, Sunita
Context . Subtyping of periampullary adenocarcinoma into intestinal and pancreatobiliary subtypes has emerged as an important prognostic factor with potential therapeutic implications. This distinction on morphology alone is often difficult with significant interobserver variability. Objective . To analyze the usefulness of a panel of immunohistochemistry (IHC) markers as an aid to morphologic subtyping of periampullary adenocarcinoma. Design . A total of 172 periampullary adenocarcinomas were classified morphologically by 3 study pathologists. Interobserver agreement was assessed in each case. Cases were then typed using a predetermined IHC panel (comprising CK7, CK20, MUC1, and CDX2). Results . Morphologically, 66 (38.4%) cases were intestinal, 56 (32.6%) pancreatobiliary, 25 (14.5%) mixed, 16 (9.3%) poorly differentiated, 6 (3.5%) mucinous, and 3 (1.7%) signet ring cell adenocarcinoma. Concordant diagnosis was reached in 138 cases (80.2%) with moderate overall interobserver agreement (κ = 0.47). Concordance was higher in morphologically distinct mucinous (100%; κ = 0.94) and signet ring cell subtypes (100%; κ = 1.0) than in intestinal (84.6%; κ = 0.47) and pancreatobiliary (82.1%; κ = 0.43) types. Concordance was poor for mixed (64%; κ = 0.27) and poorly differentiated (68.8%; κ = 0.76) tumors. IHC subtyped 79 cases (46%) as pancreatobiliary, 73 (42.4%) as intestinal, and was inconclusive in 20 cases (11.6%). IHC helped classify 21 out of 25 (84%) mixed and 10 out of 16 poorly differentiated (62.5%) adenocarcinomas. Combination of histology and IHC classified 161 of the total 172 cases (93.6%). Conclusion . Use of an IHC panel aids in subtyping of periampullary adenocarcinomas, especially in tumors with mixed morphology and poor differentiation.